Bimetallic Nanoalloy Catalysts for Green Energy Production: Advances in Synthesis Routes and Characterization Techniques - Ashraf, Saima; Liu, Yanyan; Wei, Huijuan; Shen, Ruofan; Zhang, Huanhuan; Wu, Xianli; Mehdi, Sehrish; Liu, Tao; Li, Baojun (Small (Weinheim an der Bergstrasse, Germany), 2023)
Bimetallic Nanoalloy catalysts have diverse uses in clean energy, sensing, catalysis, biomedicine, and energy storage, with some supported and unsupported catalysts. Conventional synthetic methods for producing bimetallic alloy nanoparticles often produce unalloyed and bulky particles that do not exhibit desired characteristics. Alloys, when prepared with advanced nanoscale methods, give higher surface area, activity, and selectivity than individual metals due to changes in their electronic properties and reduced size. This review demonstrates the synthesis methods and principles to produce and characterize highly dispersed, well‐alloyed bimetallic nanoalloy particles in relatively simple, effective, and generalized approaches and the overall existence of conventional synthetic methods with modifications to prepare bimetallic alloy catalysts. The basic concepts and mechanistic understanding are represented with purposely selected examples. Herein, the enthralling properties with widespread applications of nanoalloy catalysts in heterogeneous catalysis are also presented, especially for Hydrogen Evolution Reaction (HER), Oxidation Reduction Reaction (ORR), Oxygen Evolution Reaction (OER), and alcohol oxidation with a particular focus on Pt and Pd‐based bimetallic nanoalloys and their numerous fields of applications. The high entropy alloy is described as a complicated subject with an emphasis on laser‐based green synthesis of nanoparticles and, in conclusion, the forecasts and contemporary challenges for the controlled synthesis of nanoalloys are addressed. Bimetallic Nanoalloys catalysts are strikingly popular for green energy production and storage. Synthetic methods such as chemical reduction, vapor deposition, pyrolysis, laser ablation, etc., can improve the alloy catalytic activity for hydrogen evolution reactions, oxygen reduction reactions, oxygen evolution reactions, and alcohol oxidation reactions. In combination with transition and other metals, Nobel metals can create highly efficient electrocatalysts.